Human-leukocyte antigen class II genes in early-onset obsessive-compulsive disorder. (28th May 2019) - Rodriguez, Natalia; Morer, Astrid; González-Navarro, E. Azucena; Gassó, Patricia; Boloc, Daniel; Serra-Pagès, Carles; Lafuente, Amalia; Lazaro, Luisa; Mas, Sergi
Abstract: Objective: The exact aetiology of obsessive-compulsive disorder (OCD) is unknown, although there is evidence to suggest a gene–environment interaction model. Several lines of evidence support a possible role of the immune system in this model. Methods: The present study explores the allele variability in HLA genes of class II ( HLA-DRB1, HLA-DQB1 ) in a sample of 144 early-onset OCD compared with reference samples of general population in the same geographical area. Results: None of the 39 alleles identified (allele frequency >1%) showed significant differences between OCD and reference populations. Pooling the different alleles that comprised HLA-DR4 (including DRB1*04:01, DRB1*04:04 and DRB1*04:05 alleles) we observed a significantly higher frequency (X 2 1 = 5.53, P = 0.018; OR = 1.64, 95% CI 1.08–2.48) of these alleles in the early-onset OCD sample (10.8%) than in the reference population (6.8%). Conclusions: Taking into account the role of HLA class II genes in the central nervous system, the results presented here support a role of the immune system in the pathophysiological model of OCD.